1996
DOI: 10.1016/s0022-5223(96)70135-6
|View full text |Cite
|
Sign up to set email alerts
|

Coronary-coronary bypass graft: An arterial conduit–sparing procedure

Abstract: From May 1989 to December 1995, 143 patients underwent myocardial revascularization with one (138 patients) or two (five patients) coronary-coronary bypass grafts in addition to other bypass grafts, for a total of 463 distal anastomoses (mean 3.2 +/- 0.6 per patient). Coronary-coronary bypass grafts were chosen for the following reasons: arterial conduit-sparing procedure, inadequate length for in situ graft, calcified ascending aorta, and stenosed or occluded subclavian arteries. One hundred eleven arterial g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…Nottin et al reported only three patients with CCBG where ITA (LITA in two, right internal thoracic artery [RITA] in one patient) was used as the conduit in CCBG, LAD‐LAD bypasses. They reported early patency of 98%, six in their series 2 . Nezic et al presented mid‐term follow‐up of a patient with CCBG of LAD with LITA graft after 3.5 years 9 .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Nottin et al reported only three patients with CCBG where ITA (LITA in two, right internal thoracic artery [RITA] in one patient) was used as the conduit in CCBG, LAD‐LAD bypasses. They reported early patency of 98%, six in their series 2 . Nezic et al presented mid‐term follow‐up of a patient with CCBG of LAD with LITA graft after 3.5 years 9 .…”
Section: Discussionmentioning
confidence: 95%
“…The hemodynamic superiority of CCBG over aortocoronary bypass has been documented by many authors. Proximal anastomoses constructed on the coronary artery itself provide more physiologic diastolic blood flow pattern and less Venturi effect as compared to grafts anastomosed to the aorta or the subclavian artery that are far from the sinuses of Valsalva of the aorta and are unable to use the advantages of the coronary‐prompting effect of the sinuses 1,2 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CCBG was first performed by Rowland and Grooters 6 . In CCBG, the anastomoses are performed between two segments of the same coronary artery or between different coronary arteries 7,8 . Arterial grafts are the first choice for this procedure.…”
Section: Discussionmentioning
confidence: 99%